2017
DOI: 10.1038/srep41131
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone-Like Hormone is a Poor Prognosis Marker of Head and Neck Cancer and Promotes Cell Growth via RUNX2 Regulation

Abstract: Parathyroid Hormone-Like Hormone (PTHLH) is an autocrine/paracrine ligand that is up-regulated in head and neck squamous cell carcinoma (HNSCC). However, the cellular function and regulatory mechanism in HNSCC remains obscure. We investigated the clinical significance of PTHLH in HNSCC patients, and verified the role of RUNX2/PTHLH axis, which is stimulated HNSCC cell growth. In patients, PTHLH is a poor prognosis marker. PTHLH expression lead to increasing the cell proliferation potential through an autocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 48 publications
6
39
2
Order By: Relevance
“…Besides its physiologic role as master regulator of osteogenic differentiation, several studies confirmed the tumor‐promoting role of RUNX2 in different cancer entities, including HNSCC (22, 36–39). Ectopic RUNX2 expression leads to an increased parathyroid hormone–like hormone expression and promotes proliferation of HNSCC cells (40). Moreover, RUNX2 was up‐regulated in HNSCC with lymph node metastasis and predicted poor prognosis in patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its physiologic role as master regulator of osteogenic differentiation, several studies confirmed the tumor‐promoting role of RUNX2 in different cancer entities, including HNSCC (22, 36–39). Ectopic RUNX2 expression leads to an increased parathyroid hormone–like hormone expression and promotes proliferation of HNSCC cells (40). Moreover, RUNX2 was up‐regulated in HNSCC with lymph node metastasis and predicted poor prognosis in patients with HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells are one source of PTHrP, which causes humoral hypercalcemia and promotes the osteolytic bone metastases of a malignancy by activating the type 1 PTH/PTHrP receptor (PTH1R) in the kidneys and skeleton [36]. PTHrP is also implicated in the regulation of the behavior of primary cancer by the paracrine/autocrine action model, including cell proliferation, migration, and invasion, and prevents cell death in different types of cancers [37,38,39]. PTHrP supports the metastatic potential of prostate cancer by protecting tumor cells from anoikis in both in vitro and in vivo models [40].…”
Section: Discussionmentioning
confidence: 99%
“…PTHLH aids in regulating cell differentiation and proliferation, particularly in bone development, and promotes cell migration and invasion [16,17]. A significant prevention of apoptosis has also been observed with PTHLH upregulation [15]. RUNX2 (runt-related transcription factor 2), another gene involved in osteoblast differentiation, may stimulate PTHLH expression through IHH (Indian Hedgehog) [15], both of whose expressions are upregulated in our metastatic model when compared to the muscle model (Figure 4a).…”
Section: Discussionmentioning
confidence: 62%
“…The 47 genes identified in the mouse comparison were analyzed across the human tumors, and only one gene was found to be significantly different: parathyroid hormone-like hormone (PTHLH) (p-value = 0.0391, 95% CI = −2.56 to −0.068) (Figure 4c) (Supplemental Table S3). This gene is intriguing in that it is downstream of RUNX2, a master regulator of bone development and ossification, and a high expression has been correlated to a faster disease progression in a number of cancers (i.e., colon, prostate, breast, head, and neck) due to the overexpression of PTHLH [15][16][17][18]. Among its putative functions for cancer progression is the activation of myeloid-derived suppressor cells (MDSCs) in the bone marrow [18].…”
Section: Underlying Gene Expression Of Bone Development Genes In Metamentioning
confidence: 99%